Design, Synthesis, and Evaluation of Near Infrared Fluorescent Multimeric RGD Peptides for Targeting Tumors - Ye, Yunpeng (2006)
Molecular interactions between RGD peptides and integrins are known to mediate many biological and pathological processes. This has led to an increased interest in the development of RGD compounds with high affinity and improved selectivity for integrin receptors. In this study, we synthesized and evaluated a series of multimeric RGD compounds constructed on a dicarboxylic acid-containing near infrared (NIR) fluorescent dye (cypate) for tumor targeting. An array of NIR fluorescent RGD compounds were prepared efficiently, including an RGD monomer (cypate-(RGD)(2)-NH(2)), two RGD dimers (cypate-(RGD)(2)-NH(2) and cypate-(RGD-NH(2))(2)), a trimer (cypate-(RGD)(3)-NH(2)), two tetramers (cypate-(RGD)(4)-NH(2) and cypate-[(RGD)(2)-NH(2)](2)), a hexamer (cypate-[(RGD)(3)-NH(2)](2)), and an octamer (cypate-[(RGD)(4)-NH(2)](2)). The binding affinity of the multimeric RGD compounds for α(v)β(3) integrin receptor (ABIR) showed a remarkable increase relative to the monomer cypate-RGD-NH(2). Generally, the divalent linear arrays of the multimeric RGD units bound the ABIR with slightly higher affinity than their monovalent analogues. These results suggest that the receptor binding affinity was not only dependent on the number of RGD moieties but also on the spatial alignments of the pendant peptides. Internalization of the compounds by ABIR-positive tumor cells (A549) was monitored by NIR fluorescence microscopy. The data showed that endocytosis of the octameric RGD derivative was significantly higher by comparison to other compounds in this study. In vivo noninvasive optical imaging and biodistribution data showed that the compounds were retained in A549 tumor tissue. These results clearly demonstrated that an array of simple RGD tripeptides on a NIR fluorescent dye core can be recognized by ABIR. Optimization of the spatial alignment of the RGD moieties through careful molecular design and library construction could induce multivalent ligand-receptor interactions useful for in vivo tumor imaging and tumor-targeted therapy.